PSYCHOLOGICAL EFFECTS OF THE EXPOSURE TO TRAFFIC IN PROFESSIONALS AND NOVICE DRIVERS - Sáiz Vicente, Enrique; Chisvert Perales, Mauricio; Bañuls Egeda, Rosa (Anales de Psicología / Annals of Psychology)
This work offers an empirical approximation to the problems of the emotional variable anxiety in a professional drivers sample and novice. This emotional reaction is present in a high number of injured subjects, in addition to be other of the emotions that more cite the persons when drive. The investigation tries the study of the own traffic situation as generating of anxiety, measure through Inventario de Situaciones Ansiógenas en el Tráfico (ISAT, Bañuls, 1993).Our objective is centered in determining if actually the exposition to the traffic, greater obviously in the professional drivers, generates greater anxiety levels in these, in comparison with the conductors novice, as well as to show what potentially generating situations of anxiety are related to the accident rates in both samples of drivers.The novice drivers punctuate significantly higher than the professional drivers in those designated situations of external evaluation and those than external impediments and withholdings, while, the professionals underline in those situations that denote self-evaluation of the subject and those that imply critical and aggression originating from the drivers of other vehicles.